Genetics of psoriasis – from serological studies of human leukocyte antigens to whole genome association studies - Szczerkowska-Dobosz, Aneta; Rębała, Krzysztof (Dermatology Review/Przegląd Dermatologiczny, 2011)
Psoriasis is a complex disease with multifactorial mode of inheritance, which means that its clinical manifestations depend upon multiple genes interacting with environmental agents. The major genetic factor responsible for 35-50% susceptibility for early psoriasis in the Caucasian population, HLA-Cw*06 , is located within the major histocompatibility complex (MHC) on the sixth chromosome. Whole genome association studies, the newest research trend, revealed three genetic, non-MHC related pathways connected with psoriasis susceptibility: Th17, Th2 and NF-kB-dependent. These genes are responsible for inflammation, epidermal proliferation and epidermal barrier function in psoriasis.